2012
DOI: 10.1080/09084282.2012.670160
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Semantic Associative Categories in Patients with Alzheimer's Disease

Abstract: Deterioration of semantic memory is one of the primary neuropsychological deficits caused by Alzheimer's disease (AD). In this study, we hypothesize that the breakdown of semantic memory in the mild-to-moderate stage of AD is due to the disruption of the semantic network that links the concepts. Furthermore, the loss of these links is not homogeneous through the semantic association categories (i.e., Superordinate, Contiguity, Part/Whole, Attribute, Function). Twenty-two subjects (11 patients with mild-to-mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This finding is in line with other previous findings (Di Giacomo, De Federicis, Pistelli, et al, 2012;Passafiume et al, 2012), which showed that the semantic impairment in AD starts with difficulty in using the semantic associative relationships and not with a deficit in naming of the concepts.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with other previous findings (Di Giacomo, De Federicis, Pistelli, et al, 2012;Passafiume et al, 2012), which showed that the semantic impairment in AD starts with difficulty in using the semantic associative relationships and not with a deficit in naming of the concepts.…”
Section: Discussionsupporting
confidence: 93%
“…Analyses revealed a positive correlation between the volcano item score and the category fluency test score in the group with AD. These findings suggest that lower semantic proximity in naming a specific object reflects the degree of semantic network deterioration in AD . Moreover, the findings argue for a top‐down deterioration beginning with the loss of higher‐order categories.…”
mentioning
confidence: 74%
“…One possible explanation for the present findings is drawn from research into the maintenance of verbal proficiencies in older adults, such as vocabulary, word comprehension and verbal working memory. It has been found that older adults are significantly better than young adults in verbal divergent thinking tasks, whereas the opposite is true for visual divergent thinking tasks [129]. It is therefore reasonable to postulate that verbal divergent thinking in older adults may be supported by the verbal proficiencies that remain intact across the lifespan [12].…”
Section: Plos Onementioning
confidence: 99%